Factors Predicting Turkish and Korean Students' Science and Mathematics Achievement in TIMSS 2011 - Topcu, Mustafa Sami; Erbilgin, Evrim; Arikan, Serkan (EURASIA, 2016)
This study makes an important contribution to an expanding body of international comparative studies by exploring factors predicting differences in science and mathematics achievement by students in Turkey and the Republic of Korea on the 2011 TIMSS assessment. While these countries are similar with regards to population size, cultural beliefs about education, and public expenditure on education, students in each country have different levels of achievement in science and mathematics. The current research investigated how aptitude, instruction, and environment related factors predict Turkish and Korean students' achievement in science and mathematics. In both countries, some factors, such as student aptitude (e.g., science self-efficacy) and environmental (e.g., parental educational level) factors significantly predicted students' science and mathematics achievement. However, we found some differences between the two countries regarding certain classroom environmental variables, such as bullying and student sense of belonging at school. We discuss educational implications for these findings.
Keywords: student aptitude variables; instructional variables; environmental variables; mathematics achievement; science achievement; TIMSS 2011; HIGH-SCHOOL-STUDENTS; ACADEMIC-ACHIEVEMENT; PARENTAL INVOLVEMENT; PRODUCTIVITY; PERFORMANCE; CHILDREN; OUTCOMES; FAMILY; TURKEY; MODEL; Education & Educational Research